A Study of The Impacts of Culture on Brand and Brand Management: In The Context of Chinese Spirit Industry - Sun, Xiangpei (2010)
This study investigates and discusses the impacts of culture on brand and brand management in the context of Chinese spirit industry. The study deploys the qualitative method. In addition, the individual depth interviews are conducted to collect the data needed. By adopting Hofstede‟s four dimension of culture, the finding shows that: (I) Brand is viewed as a significant equity of a company by Chinese managers; (II) there are three dimensions out of five showing impacts on brand and brand management, namely collectiveness, power distance and long term orientation; (III) there are some other Chinese thoughts can be found from the brand management in China. To conclude, the findings highlight the importance of the brand and brand management. In addition, within the Chinese spirit industry, the impacts of culture on brand and brand management are obvious.